Actualizing sustainable shrimp cultivation: Innovative knowledge transfer at Dr. Shrimp. Issue 2 (30th September 2020) - Chen, Po‐Chang; Li, Li‐Te
Abstract: Due to virus infection and unfriendly farming methods, aquatic technology has encountered a series of challenges. Though many efforts have been made, very few studies have focused on the cultivation of shrimp. Therefore, this study aimed to investigate how the founder of Dr. Shrimp transferred innovative and professional knowledge to his trainees, so as to achieve the healthy, non‐toxic, ecofriendly, and sustainable shrimp cultivation that Dr. Shrimp has consistently valued. There are five participants, including the founder, one partner, two clients, and one intern. The data were collected via interview, observation, documents, and analyzed using qualitative content analysis. The results indicated six phases of knowledge and techniques applied at Dr. Shrimp: incentives, communication, acceptance, acquisition, execution, diffusion, which helped to establish the six‐phase model for knowledge transfer and innovation diffusion. It is hoped that the findings can pave the way for other aquatic cultivation to promote sustainable cultivation.